THE EVOLVING CONCEPTUALISATION OF MEANINGFUL ENGAGEMENT IN EVICTION PROCEEDINGS: A CRITICAL ANALYSIS - ZAMANI SAUL (IJRDO - Journal of Social Science and Humanities Research, 2026)
The Constitutional Court of South Africa has unequivocally affirmed its commitment to meaningful engagement during eviction proceedings, as evident in the case of Charnell Commando and Others v City of Cape Town and Another 2025 (3) SA 1 (CC). The jurisprudential doctrine of meaningful engagement was first introduced in Occupiers of 51 Olivia Road, Berea Township and 197 Main Street, Johannesburg v City of Johannesburg 2008 (3) SA 208 (CC). Meaningful engagement during evictions encompasses both procedural and substantive safeguards for unlawful occupiers, aiming to protect the unlawful occupiers against arbitrary evictions and to uphold their dignity to prevent a repeat of inhumane apartheid-style evictions. However, the application of this doctrine has been marred by conceptual ambiguities and inconsistencies, potentially compromising the interests of vulnerable unlawful occupiers. Through an analytic doctrinal approach, this article examines relevant eviction judgments since the Occupiers of 51 Olivia Road case in 2008 and organises them into three conceptual approaches, which are transformative conceptualisation, regressive conceptualisation, and revived transformative conceptualisation. This article argues that an adjudicative emphasis on substantive safeguards of meaningful engagement is transformative and necessary for the protection of unlawful occupiers against arbitrary evictions reminiscent of apartheid-style evictions. This article is necessary as the right against arbitrary evictions is the most litigated socio-economic right in South Africa and therefore, critical evaluation of the eviction jurisprudence is essential as we approach a significant milestone of the 30 years of the democratic constitution.